2011
DOI: 10.3748/wjg.v17.i37.4242
|View full text |Cite
|
Sign up to set email alerts
|

Integration of human papillomavirus 18 DNA in esophageal carcinoma 109 cells

Abstract: Integration of the HPV genome into the host cell chromosome suggests that persistent HPV infection is vital for malignant cell transformation and carcinogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…In a previous study, HPV18 was detected and localized in human chromosome 8 in the esophageal squamous cell carcinoma EC109 cell line, which supported the hypothesis that HPV infection is a pathogenic factor in the development of esophageal cancer (11). Moreover, chronic high-risk HPV infection and the integration of elements of the viral genome into the human chromosome have proven to be pathogenic factors for cervical malignant transformation and lesions (12,13).…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…In a previous study, HPV18 was detected and localized in human chromosome 8 in the esophageal squamous cell carcinoma EC109 cell line, which supported the hypothesis that HPV infection is a pathogenic factor in the development of esophageal cancer (11). Moreover, chronic high-risk HPV infection and the integration of elements of the viral genome into the human chromosome have proven to be pathogenic factors for cervical malignant transformation and lesions (12,13).…”
Section: Introductionsupporting
confidence: 57%
“…Nevertheless, few reports (11)(12)(13)(14) have described the HPV integration site. The objective of the present study was to assess HPV18 infection and its location in the human genome in the setting of EC.…”
Section: Introductionmentioning
confidence: 99%
“…The cell lines, both primary and established, included in the present study were: 2.2.15 [27]; AM-HLH [28]; C4-I, C4-II, CaSki [29]; CU-VI-8 [30]; EC109 [31]; HeLa [29,32]; Hep3B [27,33]; hu-GK14 [34]; HX151c, HX155c, HX156c, HX160c [35]; 37]; Katata [38]; ME-180 [29]; MS1 [39]; MS-B6, MS-T6 [40]; MS751 [29,41] Overall the present analysis identified 628 viral integrants, of which 530.84 (84.53%) were transcriptionally active; in other words, 15.47% of the integrants were silent. One study regarding HHV-4 reported that 90-92% of the integrants in the screened cells were active [36]; the higher level was used herein to report the proportion of active viral centers, hence the fractional number.…”
Section: Resultsmentioning
confidence: 99%
“…The cell lines, both primary and established, included in the present study were: 2.2.15 [27]; AM-HLH [28]; C4-I, C4-II, CaSki [29]; CU-VI-8 [30]; EC109 [31]; HeLa [29,32]; Hep3B [27,33]; hu-GK14 [34]; HX151c, HX155c, HX156c, HX160c [35]; IB-4 [36,37]; Katata [38]; ME-180 [29]; MS1 [39]; MS-B6, MS-T6 [40]; MS751 [29,41]; NAB-2 [42]; Namalwa-C18 [36]; Pal-1 [43]; PCL/PRF/5 [27]; QG-U, QG-H [44]; SiHa [29,45]; SKG-I, SKG-II, SKG-III [44]; SNU-182, SNU-354, SNU-368, SNU-387, SNU-398, SNU-423, SNU-449, SNU 475 [46]; SNU-739, SNU-761, SNU-878, SNU-886 [47]; UM-SCV-6 [48]; UD-SCC-2, UD-SCC-047 [49]; UPCI:SCC090 [50]; and UPCI:SCC154 [49]. Overall the present analysis identified 628 viral integrants, of which 530.84 (84.53%) were transcriptionally active; in other words, 15.47% of the integrants were silent.…”
Section: Resultsmentioning
confidence: 99%
“…Since then, many reports in the field have supported this viewpoint [ 7 – 13 ]. Our previous work showed that high-risk HPV types 16 and 18 were detected in esophageal tumors [ 14 ], and HPV18 was localized in human chromosome 8 in the EC109 cell line [ 15 ], these results indicates that HPV infection is a pathogenic factor for esophageal cancer.…”
Section: Introductionmentioning
confidence: 98%